Peningkatan Kesiapsiagaan Anggota Nasyiatul Aisyiyah (NA) Cabang Ngawen Klaten Terhadap Bencana - Willis Diana; Yunita Furi Aristyasari; Restu Faizah; Edi Hartono (LPPM Universitas Muhammadiyah Tasikmalaya, 2020)
Increasing the skills and abilities of individuals, families and communities in the face of disasters need to be carried out continuously, because of the high potential for threats and the increasing number of people exposed to disaster risk. Women have a strategic role in disaster management and are very effective in transferring their knowledge to the next generation. In this community service activity, the Nasyiatul Aisyiyah branch of Ngawen, Klaten, Central Java, chosen as a partner. The purpose of this activity is to improve women's preparedness capacity and to reduce people's exposure to disasters. The activities are not only in terms of physical preparedness but also spiritual preparedness. This community service activity consist of three stage, which are,the first stage is preliminary survey to assess the knowledge of participants on disaster preparedness, the second stage is giving disaster preparedness education with facilitators guidance, providing disaster preparedness pocket books, and discussions, and the final stage was an assessment of disaster preparedness after participants are given education/training. The assessment was done using a questionnaire. The result of the prelimanary survey show that the participant are at the level of moderate preparedness. The disaster preparedness education increasing all the disaster preparedness parameters index. The knowledge parameter index increased by 5%, the family preparedness plan parameter index increased by 15%, the parameter index of disaster warning knowledge increased by 6%, the resource mobilization parameter index increased by 10%. The socialization or simulation is needed about the importance of evacuation, relief and rescue, and campaign about the disaster is also needed through various media that are in accordance with the conditions of the community.